The Association of Age and Number of Parturition with Mammary Gland Tumor Case Rate in Mice in Malang Raya - Wukirani, Maulidi Robingi Mardiyani; Adha, Essly Hervianingsih; Dewi, Sang Ayu Putri Aristya; Setianingrum, Ani; Pratama, Dyah Ayu Oktavianie Ardhiana; Hardian, Andreas Bandang (Universitas Airlangga, 2022)
Mammary gland tumours are frequently reported in adult female mice. It broadly affects the productivity and breeding performance of mice in breeding centres. The tumours might occur spontaneously due to internal factors such as genetic mutation and hormonal disturbance, however, external causes such as Mouse Mammary Tumour Virus (MMTV) infection was also reported. This study aimed to prove that age and number of parturition associate with mammary gland tumour case rate in female mice in Malang Raya. Chi-square tests were employed to analyse the association between risk factors and mammary gland tumour case rate in this study. Histopathologic analysis described three subtypes of mammary gland tumours in mice which were adenoma, adenocarcinoma type A and adenocarcinoma type B. Chi-square tests results of tumour case rate toward age and number of parturitions were consecutively 0,004 and 0,0025 which indicated that age and number of parturitions were associated with mammary gland tumours case rate in mice in Malang Raya. The mapping of tumour case distribution visually showed a trend that higher disease proportions were spotted in higher altitude of sampling location. This might relate to the geographical breeding characteristics or temperature which needs further study to explore the association of spatial factors with the mammary tumour incidence in mice.